Implementasi Lesson Study sebagai Upaya Meningkatkan Kualitas Mengajar Guru di SMP IT Khairunnas Kota Bengkulu - Bendriyanti, Rita Prima; Dewi, Citra; Apriadi, Hengki (CV. Creative Tugu Pena, 2022)
The research was conducted to achieve the goal of analyzing the lesson study process as an effort to guide teachers in improving teaching quality. The research method was carried out in a descriptive qualitative manner through direct observation or observation, interviews, and documentation. Based on the interviews that have been carried out and the documentation that has been carried out on lesson study planning, it was found that there were several obstacles experienced by the model teacher when teaching, including not being confident in teaching, little experience, lack of mastery of teaching techniques and the use of methods and media used in monotonous learning, as well as unfinished assessment techniques. Besides this, the observer or senior lecturer has suggestions for improvement in the form of selecting methods that vary according to the topic, using innovative media, and assessments that focus on process assessment. At the implementation stage, it was found that the model teacher had carried out the lesson according to the previously agreed plan with the observer lecturer. However, regarding its implementation in the classroom, there are still some weaknesses that must be corrected, such as the use of learning media and technology, as well as the ability to present material during lecture sessions. As the next stage, namely the reflection stage, an FGD was carried out which resulted in improvements for the planning and implementation of the next stage. Keywords: Teacher Quality, Implementation Lesson Study, Inreasing Teacher Quality